PELATIHAN PEMBUATAN HANDYCRAFT DI PONDOK PESANTREN TARBIYATUL QUR’AN (PPTQ) AR-ROHMAH DESA CODO KECAMATAN WAJAK KAB. MALANG - Mila Suraya; Ana Faizatus Sholichah (Jurnal Interaktif: Warta Pengabdian Pendidikan, 2022)
Santri are students who have the potential to hone and develop their skills. One of these skills includes the business of making handicrafts. The objectives of the Handy Craft Making training are: (1) Putri Madratsah Diniyah PPTQ Ar-Rohmah students; (2) female students of Pondok PPTQ Ar-Rohmah; and (3) female students at the Ar-Rohmah Al-Qur'an Education Park. The strategy for implementing the Handy Craft training in Codo Village, Wajak District, is as follows: The preparation stage, the Implementation Stage, While the final stage is an evaluation of the work program. The implementation of the Handy craft training was carried out at the Ar-Rohmah Tarbiyatul Qur'an Islamic Boarding School (PPTQ) by making 2 initial visits. Where the first visit was the UM KKN team asking permission from the caretaker of the cottage, and the second was regarding discussing the schedule that would be used for training. After making the initial visit, the UM KKN team conducted training with approximately 6 meetings according to the schedule that had been made and agreed upon by the cottage caretakers and also the UM KKN team. Handy Craft making training at PPTQ Ar-Rohmah shows an achievement of 85%. These results are obtained from the achievement or failure to achieve the objectives of the training program to the fullest according to the initial planning and objectives of the program.